Diameters and Fluorescence Calibration for Extracellular Vesicle Analyses by Flow Cytometry - Simeone, Pasquale (Int J Mol Sci, 2020)
Extracellular vesicles (EVs) play a crucial role in the intercellular crosstalk. Mesenchymal stem cell-derived EVs (MSC-EVs), displaying promising therapeutic roles, contribute to the strong rationale for developing EVs as an alternative therapeutic option. EV analysis still represents one of the major issues to be solved in order to translate the use of MSC-EV detection in clinical settings. Even if flow cytometry (FC) has been largely applied for EV studies, the lack of consensus on protocols for FC detection of EVs generated controversy. Standard FC procedures, based on scatter measurements, only allows the detection of the “tip of the iceberg” of all EVs. We applied an alternative FC approach based on the use of a trigger threshold on a fluorescence channel. The EV numbers obtained by the application of the fluorescence triggering resulted significantly higher in respect to them obtained from the same samples acquired by placing the threshold on the side scatter (SSC) channel. The analysis of EV concentrations carried out by three different standardized flow cytometers allowed us to achieve a high level of reproducibility (CV < 20%). By applying the here-reported method highly reproducible results in terms of EV analysis and concentration measurements were obtained.